Restless Legs Syndrome/Willis Ekbom Disease : Long-Term Consequences and Management - Manconi, Mauro; García-Borreguero, Diego (Springer New York : Imprint: Springer, 2017)
Due to the fact that Restless Legs Syndrome/Willis-Ekbom Disease is usually a chronic condition, this book aims to provide physicians with the necessary tools for the long-term management of patients with RLS. The first part of the book addresses the various comorbidities and long-term consequences of RLS on life quality, sleep, cognitive, psychiatric and cardiovascular systems, while the second part focuses on the management of long-term treatment and the drug-induced complications in primary RLS and in special populations. Written by experts in the field, this practical resource offers a high-quality, long-term management of RLS for neurologists, sleep clinicians, pulmonologists and other healthcare professionals.- Resumé vydavatel
Keywords: syndrom neklidných nohou; poruchy spánku; kvalita života; restless legs syndrome; sleep disorders; quality of life; elektronické knihy; sborníky; electronic books; papers of several authors